2011
DOI: 10.1016/j.jcf.2010.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Lactate in cystic fibrosis sputum

Abstract: Successful antibiotic therapy is reflected by a decrease in lactate concentrations. Neutrophils are the most likely source for lactate in sputum of CF patients. Therefore lactate may be used to monitor responses to antibiotic therapy as an adjunct to lung function measurements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
54
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 37 publications
3
54
0
Order By: Relevance
“…through fermentation [48]. Lactate has been detected in the CF sputum at a mean concentration of 3 mM, and higher concentrations have been correlated with lower lung function [49]. Because LDHs enable cells to use lactate as an energy source for growth and reproduction, they are considered as virulence factors.…”
Section: Resultsmentioning
confidence: 99%
“…through fermentation [48]. Lactate has been detected in the CF sputum at a mean concentration of 3 mM, and higher concentrations have been correlated with lower lung function [49]. Because LDHs enable cells to use lactate as an energy source for growth and reproduction, they are considered as virulence factors.…”
Section: Resultsmentioning
confidence: 99%
“…The lactate so produced is also a chemoattractant for immune cells (Lardner, ). In addition, formalin injection causes an immense infiltration of neutrophils, which are an authentic source of lactate (Simchowitz and Textor, ; Bensel et al, ), at the site of localized inflammation because of the altered mitochondrial metabolism (Jha et al, ). Moreover, we previously reported that lactate levels are substantially increased at the local inflammation site following intraplantar inflammatory challenge (Jha et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Further study will be necessary to confirm the extent to which lactate is taken up and utilized by ATII cells when glucose is also present; however, this work establishes that ATII cell glucose metabolism is responsive to extracellular lactate. This may have considerable implications for ATII cell function in disease, since plasma lactate can exceed 20 mM in extreme cases of hypoxia or hypotension (25), and pulmonary tissue concentrations increase more than twofold from normal levels in idiopathic pulmonary fibrosis (IPF) patient parenchymal tissue (22) and possibly in cystic fibrosis, based on elevated lactate measured in patient sputum samples (1).…”
Section: Discussionmentioning
confidence: 99%